LA SEDUCCIÓN PUBLICITARIA EN MAD MEN - Dra. Begoña GUTIÉRREZ-MARTÍNEZ (Fonseca, Journal of Communication, 2023)
We focus on Mad Men (Matthew Weiner, 2007-2015, USA), a television series that deals with the world of advertising on Madison Avenue in New York. Set in the 1960s, the series stages the Golden Age of advertising that takes place during that period. This is a period in which new advertising formulations are tested. Representation strategies change, leaving behind argumentative models, to develop more seductive ones